2022
DOI: 10.3390/cells11152360
|View full text |Cite
|
Sign up to set email alerts
|

Whole Transcriptome Analysis Identifies Platycodin D-Mediated RNA Regulatory Network in Non–Small-Cell Lung Cancer

Abstract: Non–small-cell lung cancer (NSCLC) is one of the most fatal malignant tumors harmful to human health. Previous studies report that Platycodin D (PD) exhibits anti-tumor effects in multiple human cancers, including NSCLC, but the underlying mechanisms are largely unknown. Accumulating evidence indicates that non-coding RNAs (ncRNAs) participate in NSCLC disease progression, but the link between PD and the ncRNAs in NSCLC is poorly elucidated. Here, we used whole transcriptome sequencing to systematically invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…And this effect should be correlated with cholesterol ( Bailly and Vergoten, 2020 ). Zheng et al (2022) also identified the PD-mediated RNA regulatory network in NSCLC through the whole transcriptome analysis. That is to say, PD inhibits cell proliferation, arrests the cell cycle, and induces cell apoptosis through targeting BCL2-related proteins.…”
Section: Pharmacology Of Pldmentioning
confidence: 99%
“…And this effect should be correlated with cholesterol ( Bailly and Vergoten, 2020 ). Zheng et al (2022) also identified the PD-mediated RNA regulatory network in NSCLC through the whole transcriptome analysis. That is to say, PD inhibits cell proliferation, arrests the cell cycle, and induces cell apoptosis through targeting BCL2-related proteins.…”
Section: Pharmacology Of Pldmentioning
confidence: 99%
“…As a traditional herbal medicine, platycodin D (PD) is the major bioactive monomer derived from Platycodon grandiflorum (P. grandiflorum) and is used as an expectorant for pulmonary disease in Asia [ 2 ]. We previously found that PD exhibits anticancer effects on NSCLC through noncoding RNA (ncRNA) regulation [ 3 ]. Although the RNA methylome is a hotspot in ncRNA regulation studies, especially for N 7 -methylguanosine (m 7 G) modification, in-depth pharmacological studies related to this topic are limited [ 4 ].…”
mentioning
confidence: 99%